Upplevelser av fysisk aktivitet i ett slättlandskap - Persson, Ann (2007)
Regular physical activity provides many chronic diseases and is an important contributor to health promotion. According to Swedish goals for public health, community planning ought to provide opportunities for exercise in all groups of the population and exercise in daily life should be uncomplicated, even in rural areas. The purpose of this study was to explore how individuals living in a flat country experienced their opportunities for exercise on a regular basis. Four semi-structured interviews were carried out with a phenomenological approach and for the analysis a phenomenological-hermeneutic method was used, resulting in two main themes and nine sub themes. The first main theme "The reciprocal relation between physical activity and the landscape" showed that the informants experienced that they had good opportunities in the landscape for physical activity, it was easy to exercise on a regular basis, provided there was motivation. They did not feel that the exercise habits were restricted by the necessity of a car. The informants expressed that nature characteristics and aesthetics values gave variation and stimulation. They chose to combine physical activity with nature experiences to gain increased feeling of well-being. More trails in the landscape, together with instructions for usability and distance to improve accessibility were needed as well as walking- and bicycle paths for road safety. The second main theme "My philosophy of life" showed that the informants experienced their childhood and mental attitude as important reasons for being motivated to physical activity. To conclude the results, the informants experienced that different kinds of nature experiences, nature characteristics, aesthetics values, stimulation, accessibility, usability and road safety were important factors for the opportunity to exercise in a flat landscape. It would be interesting in future research to explore individuals who are less physically active or sedentary. It would be particularly interesting to study if there are synergistic benefits related to well-being when being physically active in green surroundings.